Child Friendly Library Management in Fostering Students' Interest in Reading: Pengelolaan Perpustakaan Ramah Anak dalam Menumbuhkan Minat Baca Siswa - Wahyuni Lailatul Sholikha; Akhtim Wahyuni (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe the management of a child-friendly library at SDN Pagerwojo Sidoarjo and to describe the reading interest of high-class students at SDN Pagerwojo Sidoarjo. This type of research uses a qualitative case study approach. Data collection techniques used by researchers are observation, interviews, and documentation. From the results of data analysis conducted by interviewing several parties, it can be said that the management of the child-friendly library at SDN Pagerwojo is good in planning, organizing, implementing, and evaluating. With the results of good management and good implementation, the reading interest of high-class students has begun to grow. In the data analysis conducted by researchers, it was found that there are obstacles in managing child-friendly libraries, namely library management has not yet led to digital library management. Highlights: Effective library management fosters students' reading interest: The study explores the impact of child-friendly library management on the reading interest of high-class students at SDN Pagerwojo Sidoarjo. Comprehensive approach to library management: The research highlights the importance of planning, organizing, implementing, and evaluating library services to create an engaging environment for students. Transition to digital library management: The study identifies the need to incorporate digital resourcesand technologies in the child-friendly library to enhance its effectiveness and accessibility for students. Keywords: Child-friendly library, Reading interest, Library management, Qualitative case study, SDN Pagerwojo Sidoarjo